2019
DOI: 10.1051/0004-6361/201834203
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the decrease in ISM lithium at super-solar metallicities in the solar vicinity

Abstract: We propose here that the lithium decrease at super-solar metallicities observed in high-resolution spectroscopic surveys can be explained by the interplay of mixed populations that originate in the inner regions of the Milky Way disk. The lower lithium content of these stars is a consequence of inside-out disk formation plus radial migration. In this framework, local stars with super-solar metallicities would have migrated to the solar vicinity and depleted their original lithium during their travel time. To o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
60
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(68 citation statements)
references
References 43 publications
7
60
1
Order By: Relevance
“…Studies are usually concerned with the upper envelope (not shown here) in the A(Li)-[Fe/H] relation of dwarf stars, reasoning that this is closer to the original lithium abundance in the ISM, since depletion over the lifetime of stars takes place (e.g., Rebolo et al 1988;Romano et al 1999;Lambert & Reddy 2004;Guiglion et al 2016b;Cescutti & Molaro 2019;Guiglion et al 2019). This upper envelope, which will be traced by extending the metal-poor tails of the mono-age populations in Fig.…”
Section: Lithium Abundance Variation With [Fe/h]mentioning
confidence: 95%
See 1 more Smart Citation
“…Studies are usually concerned with the upper envelope (not shown here) in the A(Li)-[Fe/H] relation of dwarf stars, reasoning that this is closer to the original lithium abundance in the ISM, since depletion over the lifetime of stars takes place (e.g., Rebolo et al 1988;Romano et al 1999;Lambert & Reddy 2004;Guiglion et al 2016b;Cescutti & Molaro 2019;Guiglion et al 2019). This upper envelope, which will be traced by extending the metal-poor tails of the mono-age populations in Fig.…”
Section: Lithium Abundance Variation With [Fe/h]mentioning
confidence: 95%
“…7 assuming the scatter around the mean for all mono-r birth groups is similar. Recently Guiglion et al (2019) reasoned that the observed decline in lithium abundance at super-solar metallicity can be explained as the effect radial migration, as stars in the metal-rich tail are expected to have been born roughly in the range 2 < r < 5 kpc (see Fig. 8 by Minchev et al 2018).…”
Section: Lithium Abundance Variation With [Fe/h]mentioning
confidence: 99%
“…Every new analysis of these chemical elements in stellar atmospheres contributes to the ongoing discussion of their importance in understanding the Galaxy evolution and whether they constitute a star-planet connection (see, e.g., Delgado Mena et al 2010;González Hernández et al 2010;Brugamyer et al 2011;Petigura & Marcy 2011;Schuler et al 2011;Ramírez et al 2012;Spina et al 2016;Luck 2017;Adibekyan et al 2018;Bensby & Lind 2018;Fu et al 2018;Luck 2018a;Nissen & Gustafsson 2018;Guiglion et al 2019;Pavlenko et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the sites of lithium production are identified, but their input for the lithium enrichment of the ISM is still debatable (Bensby & Lind 2018;Fu et al 2018;Guiglion et al 2019). The poorly understood mechanisms of 7 Li depletion and/or synthesis observed in F-, G-, and K-type stars make it difficult to constrain the Galactic chemical evolution models (Cescutti & Molaro 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation